Fraction of immature granulocytes reflects severity but not mortality in sepsis. (January 2015) - Ha, Sang Ook; Park, Sang Hyuk; Park, So Hee; Park, Jae Seok; Huh, Jin Won; Lim, Chae-Man; Koh, Younsuck; Hong, Sang-Bum; Jang, Seongsoo
Abstract Objective. In order to validate immature granulocytes as a universal biomarker, we have compared the clinical relevance of the proportion of immature granulocytes (IG%), measured using Sysmex XE-2100, with other biomarkers (white blood cell, C-reactive protein, lactate and procalcitonin). Methods. This single center, retrospective study included 184 patients with sepsis admitted to an emergency department. Patients were classified into two groups: Uncomplicated sepsis and complicated sepsis (severe sepsis and septic shock). IG% and other biomarkers were evaluated and compared for predicting sepsis severity, overt disseminated intravascular coagulation (DIC) and 28 day mortality. Results. In multivariate analysis, only IG% (odd ratio [OR] 2.530, p = 0.004) and lactate (OR 4.500, p < 0.001) could discriminate between complicated and uncomplicated sepsis. The optimal cut-off value for IG% and lactate was 0.5% and 2.0 mmol/L, respectively. In subgroup analyses of complicated sepsis, IG% was related to overt DIC. However, no single biomarker could predict 28-day mortality. Conclusions. Given that IG% reflected sepsis severity and overt DIC without additional cost, IG% could be a useful biomarker in patients with sepsis. However, there is a limitation for using it as a novel biomarker in sepsis due to the disability of prediction for 28-day mortality.